Violência contra a escola: repercussões curriculares - o olhar do Conselho de Escola numa escola municipal de Santo André - Sousa, Marli Luiza de (2015)
This present study aims to undertake an analysis of violence situations against the school, identifying how violence is manifested in daily life and addressed in school curriculum. Therefore, we analyze the situation from a vision of segment representatives that are part of the Public Power and representatives that are part of the user population of the School Council. We also analyze the relation that user and local community establish with a municipal school of kindergarten and elementary school, located in Santo André outskirts, metropolitan region of São Paulo. We also have analyzed the possible repercussions of school violence in the curriculum of this school in question. To realize this study, we chose a qualitative approach, through documental analysis and semi-structured interviews that were applied to the School Council representatives, from researched municipal school. For documentary analysis, we used five Pedagogical Political Projects developed by the school community in the period between 2010 and 2014. The research intended to indicate possibilities of violence confrontation against the school, observed in periods that building are not used in teaching activities, from the perspective of school counselors, and in a light of some consolidated theoretical aspects of the phenomenon of violence and school curriculum. The challenges of building a curriculum that dialogues with the real problems, checking the possibility of school overcoming violence situation, manifested through vandalism and pillaging are numerous. However, it is a possible path to be trodden in an articulated form between the power public and civil society, seeking the construction of a school founded on the principle of education social quality, from access and permanence of the subjects and the democratic management of education. It was intended, with this study, offer clues to support schools in increasing their careers searching educational activities that minimize and eliminate vandalism scenes and depredation of public property from the stage of their recent histories